Evaluation of Growth Performance of Bamboo (Gigantochiloa sp.) in Integration with Banana (Musa Paradisiaca L.) and Misai Kucing (Orthosiphon Stamineus Benth.) - Che Soh, Norhidayah (2011)
Agroforestry is one of the agricultural designs which integrate woody perennial and agricultural crop. The choice of species and system in agroforestry practice is very important to ensure its productivity. In Malaysia, various agroforestry designs were introduced but the application still limited due to the socio economic problems and also lack of knowledge. Bamboo is one of the suitable species for agroforestry practices because of its various uses and fast growing botanical species. The objectives of the study are to determine the best species between Orthosiphon stamineus and Musa paradisiaca suitable for integrating with Gigantochloa brang in term of growth performance and secondly to determine the best fertilizer between NPK and chicken dung and its rate produce highest growth performance for Gigantochloa brang with Orthosiphon stamineus, and Musa paradisiaca L. in Peninsular Malaysia. Three different plots were established with the first plot consisting of bamboo integrated with Pisang berangan (Musa paradisiaca), the second plot consisting of bamboo integrated with Misai kucing (Orthosiphon stamineus), and the third plot consisting of only bamboo species. Planting distance of bamboo culm in each plot was 4m x 4m while banana and O. stamineus were planted in between of bamboo rows. Two types of fertilizers used were Chicken dung and NPK with four different rates applied. The rates were 0, 0.5, 1.0 and 1.5 kg per clump for bamboo and banana while for each Misai kucing 0, 0.05, 0.1, and 0.150 g were applied for both fertilizers. The experiment involved eight replicates with 24 treatments all together. Growth performance data were collected every month for a period of six months and analyzed by using statistical analysis ANOVA. There were some significant difference present on bamboo growth which is for dbh and the number of culm. Bamboo integrated with O. stamineus gave the highest growth for both parameter compared with other plot. For various type of fertilizer’s application, there were significant differences detected in every parameter, but further analysis for different rates of fertilizer, only two parameters showed significant differences which were dbh and number of culm. Application of 0.5 kg NPK per clump gave the highest growth performance of dbh and number of culm. For banana growth, the significant differences were shown for every parameter (stem DBH, height, number of shoot and fruit) when analyzed with different rate of fertilizers. The application of 1.0 kg of chicken dung gave the highest height and bigger DBH. Highest number of shoots and banana bunch were produced with the application of 1.5 kg chicken dung. There were no significant difference in height and crown of O. stamineus but there was a significant difference found on the wet and dry weight of it. Application of 0.1 kg of NPK gave the highest wet weight and 0.05 kg of NPK produced the highest dry weight. The most suitable species to integrate with bamboo in term of producing best growth rate is O. stamineus and application of 0.5 kg NPK was the best rate of fertilizer applied to produce the highest growth for bamboo. Further studies on different planting distance of bamboo are recommended and the soil chemical characteristic should be done before study was carried out. Besides that, time of study should be longer to get more accurate observation.